(In)visible architecture: An exploration of food in the domestic space - Fatimah Indonesia Saffana Zayn; Paramita Atmodiwirjo (ARSNET, 2022)
This paper investigates the notion of visibility and invisibility in architecture as a framework for exploring the existence of food in the domestic area. The paper argues that there is a disconnection between food, people, and the process behind it in everyday life. Such disconnection demonstrates the alternating visible and invisible existence of food process. Exploring both existences becomes essential to reveal the overall spatial story of food. The paper explores these two aspects through the food journey in the domestic space, creating a micro investigation of how food is obtained, prepared, cooked, and served. This paper aims to examine the possibilities of outlining the complex programming in everyday systems driven by the visibility and invisibility of food in domestic settings. Based on the findings of this study, the paper develops a form of programming titled (In)visible architecture, which constructs the co-existence between visible and invisible. Using exploration of tracing, mapping, and design mechanisms, such programming aims to reveal the complex visibility of everyday systems and, by doing so, broaden the relevance of knowledge of food-based architectural design.